Secondary aorto-duodenal fistula successfully treated with a novel surgical method: A case report. (2020) - Tsuneki, Takao; Yuasa, Yasuhiro; Fukuta, Mizuki; Maki, Hidenori; Matsuo, Yuta; Mori, Osamu; Eto, Shohei; Fujiwara, Satoshi; Tomibayashi, Atsusi; Otani, Takashi
Highlights: Our patient had previously undergone artificial blood vessel replacement. He was subsequently diagnosed with a secondary aorto-duodenal fistula. During duodenal segmental resection, the syringeal part was not opened. This avoided pollution of the operative field. There has been no relapse of infection for 3 years after surgery. Abstract: Introduction: Secondary aorto-duodenal fistula (sADF) is a complication of abdominal aorta artificial blood vessel replacement that often leads to death. However, an optimal operative method has not yet been established. We describe a patient who underwent artificial blood vessel reimplantation and duodenectomy after endovascular aneurysmal repair (EVAR) with positive outcomes. Presentation of case: An 84-year-old man underwent artificial blood vessel replacement in 2015. In September 2016, he visited our emergency department and was diagnosed with sADF based on computed tomography. Urgent EVAR was performed, followed by duodenal segmental resection on the next day without opening the syringeal part to minimize the pollution of the operative field. Artificial blood vessel reimplantation and omental flap transposition were performed. As of 2020, about 3 years after surgery, there has been no relapse of the infection. Discussion: Using our novel operative method, we can minimize exposure of the artificial blood vessel and surrounding tissue to intestinal juice and pus. We believe that this reduces the risk of postoperative artificial blood vessel reinfection. Conclusion: Controlling bleeding by EVAR and resection of the duodenum and artificial blood vessels as a group without opening the syringeal part can contribute to positive long-term results as this method minimizes the pollution of the duodenectomy surgical field.